Pengaruh Pemeriksaan Pajak, Omset, Dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Hotel Dan Restoran Di Kabupaten Jepara - Yanto Yanto (Jurnal Akuntansi dan Perpajakan, 2020)
Jepara many hotels and restaurants need to know compliance in tax payments, so the formulation of the problem in this research is how the influence of tax audits, turnover and tax penalties on hotel and restaurant taxpayer compliance in Jepara Regency? The purpose of this study was to analyze the effect of tax audits, turnover and tax sanctions on hotel and restaurant taxpayer compliance in Jepara Regency. The research sample is 104 hotel and restaurant taxpayers registered with the Regional Financial and Asset Management Agency of Jepara Regency. Data analysis tools used are multiple linear regression test and hypothesis test t. The results of data analysis revealed that the tax audit had a significant positive effect on hotel and restaurant taxpayer compliance in Jepara Regency, as evidenced by the significant value of 0,000; Tax sanctions have a significant positive effect on hotel and restaurant taxpayer compliance in Jepara Regency as evidenced by a significant value of 0.012; and Turnover does not affect the compliance of hotel and restaurant taxpayers in Jepara Regency proven by a significant value of 0.100. DOI: 10.26905/ap.v6i1.4126